Politik Simbolik dan Resistensi Kultural Anak Muda Menjelang HUT ke-80 RI: Analisis Wacana Pengibaran Bendera One Piece - Hasan Labiqul Aqil; Danang Puji Atmojo (JURNAL NAWALA POLITIKA, 2025)
This study aims to examine the hoisting of the One-Piece flag as a form of symbolic politics and cultural resistance among Indonesian youth during the 80th Independence Day commemoration. The main issue is how popular culture symbols serve as a medium for critiquing social injustice and corruption. Employing Norman Fairclough’s critical discourse analysis, this qualitative research analyzes Tempo news coverage and social media discourse. Findings reveal that the Jolly Roger symbolizes solidarity and freedom, challenging the state’s narrative that frames it as a threat. Youth leverage transnational popular culture to construct alternative political identities in the digital era. The study concludes that this symbolic politics reflects a shift in political contestation toward the cultural sphere, suggesting that youth expressions should be recognized as legitimate political participation rather than threats.